Pendidikan Guru: “Pembebas atau Pembelenggu” - Asharini, Nursamsiah (Bina Nusantara University, 2013)
Each person will use their cultural knowledge in the interaction, likewise with teachers in their interaction with the students. Knowledges as a teacher, how to educate, and education are learned by the candidate when she/he studies at a teaching insitute of higher learning. Interaction between teacher and students in the classroom reflects the education done in the institute, and become student cultural knowledge.